Effect of multi-strain probiotics on the performance of AA+ male broilers - Zou, Qiangqiang; Meng, Weishuang; Wang, Tieliang; Liu, Xiao; Li, Desheng (Frontiers in Veterinary Science, 2022)
The aim of the experiment was to investigate the effects of a probiotic complex (PC) consisting of Bacillus subtilis, Clostridium butyricum and Enterococcus faecalis on productive performance, carcass traits, immune organ indices, fecal microbiota counts and noxious gas emissions in AA+ male broilers. Three hundred and sixty 1-day-old AA+ male broilers with similar body weight (44.77 ± 0.25) were randomly divided into 3 treatment groups of 6 replicates each, with 20 broilers in each replicate. The experimental groups consisted of a group fed a basal diet and groups fed basal diet supplemented with 0.1 and 0.2% PC. The results showed that the addition of PC had no significant effect (P > 0.05) on growth performance, and carcass traits of AA+ broilers during the experimental period (1–42 days of age). Dietary addition of PC significantly increased the thymus index of AA+ broilers (P < 0.05), reduced the number of E. coli and Salmonella in feces (P < 0.01) and reduced the concentrations of fecal NH3 and H2S emissions (P < 0.01). Furthermore, birds fed 0.2% PC diet had the highest number of fecal Lactobacillus counts. Results indicate that probiotic complex consisting of Bacillus subtilis, Clostridium butyricum and Enterococcus faecalis enhances immune organ development, reduces the number of E. coli and Salmonella in feces, increases the number of Lactobacillus and reduces NH3 and H2S emissions in feces. This trial provides a theoretical basis for the use of probiotic complexes in broiler production.